Differences in Proprioception Between Young and Middle-Aged Adults With and Without Chronic Low Back Pain - Pinto, Sabina M.; Cheung, Jason P. Y.; Samartzis, Dino; Karppinen, Jaro; Zheng, Yong-ping; Pang, Marco Y. C.; Wong, Arnold Y. L. (Frontiers in Neurology, 2020)
Introduction: While young adults with chronic low back pain (CLBP) exhibit impaired lumbar proprioception, it remains unclear if the same phenomenon is observed in middle-aged adults with CLBP. Objectives: This study aimed to investigate whether young or middle-aged adults with CLBP displayed different proprioception ability as compared to age-matched asymptomatic controls. Methods: Sixty-four young adults with [median age:34 [interquartile range (IQR): 29–37] years] and without [median age:29 (IQR; 23–34) years] CLBP, and 87 middle-aged adults with [median age:53 (IQR: 49–58) years] and without [median age: 54 (IQR: 45–64) years] CLBP underwent postural sway tests on a force-plate with (unstable surface) and without a foam (stable surface), while bilateral L5/S1 multifidi and triceps-surae were vibrated separately. An individual's proprioception reweighting ability was estimated by relative proprioceptive reweighting (RPW). Higher RPW values indicate less reliance on lumbar multifidus proprioceptive signals for balance. Participants also underwent lumbar repositioning tests in sitting to determine repositioning errors in reproducing target lumbar flexion/extension positions. Results: Young adults with CLBP demonstrated significantly higher median RPW values than age-matched asymptomatic controls for maintaining standing balance [stable surface: CLBP: 0.9 (IQR: 0.7–0.9), asymptomatic: 0.7 (IQR: 0.6–0.8), p < 0.05; unstable surface: CLBP: 0.6 (IQR: 0.4–0.8), asymptomatic: 0.5 (IQR: 0.3–0.7), p < 0.05]. No significant differences in repositioning error were noted between young or middle-aged adults with and without CLBP (p > 0.05). RPW values were unrelated to repositioning errors in all groups (p > 0.05). Conclusion: Young adults with CLBP, and middle-aged adults with and without CLBP had inferior proprioceptive reweighting capability. This finding may indicate potential age-related deterioration in central and peripheral processing of lumbar proprioceptive signals. Future studies should use advanced imaging and/or electroencephalogram to determine mechanisms underlying changes in proprioceptive reweighting in middle-aged adults.